ALBUM SUARA (REPERTOIRE) KATAK SERASAH Leptobrachium hasseltii TSCHUDI, 1883 DI SITU GUNUNG - Sasi Kirono; Mirza D. Kusrini; Yeni A. Mulyani (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
This study describes the vocal repertoire of forest litter frog Leptobrachium hasseltii from Situgunung Resort, Mount Gede Pangrango National Park. Two types of calls were identified: advertisement call and aggressive call. Each types were represented by two different characteristics thus four types of calls were examined. The kruskall and wallis test was used to test the difference of nine features. Pearson’s correlation test also used to determine the relationship of all call features to air temperature and body size. Dominant frequency of all call types was relatively similar. Advertisement calls type I was emitted in short duration and fewer notes than advertisement call type II. Aggressive call type I and have longer call duration compared to both of advertisement call. However the introductory note of aggressive call type II was more longer than the others. Aggressive call of L. hasseltii tended to be discrete (territorial and encounter) and represented two different continuums. This were caused by the extreme differences of both calls in duration and distance between males when emitting calls. Dominan frequencies of all call types inverse correlated with body size of frogs. Most of temporal features of advertisement call type II correlated with body size and only call duration were longer with increasingly air temperature. Interpulse-interval and pulse period were more longer by increasing the body size, while the introductory note, pulse rate and pulse repetition rate were becoming shortened and it could predict male body size to facilitated competition between males, thus serves as mate selection indicator. Key words: advertisement call, agressif call, Leptobrachium hasseltii, Situgunung resort, social interaction